Titanium Organic Complex Improves Pollination and Fruit Development of Remontant Strawberry Cultivars under High-Temperature Conditions - Monika Bieniasz; Anna Konieczny; Jan Błaszczyk; Jacek Nawrocki; Michał Kopeć; Monika Mierzwa-Hersztek; Krzysztof Gondek; Tomasz Zaleski; Jarosław Knaga; Michał Pniak (Agriculture, 2022)
Heat stress negatively affects pollination, fertilization, and consequently, the development of strawberry fruits. It was proved that foliar application of titanium organic complex improved pollination and fertilization processes of some plant species, which resulted in better fruit development. Therefore, a three-year experiment was designed to determine the effect of the titanium organic complex on pollination and fertilization processes and consequently on fruit development of three remontant strawberry cultivars grown under canopies, under conditions of high temperature. The experiment demonstrated that high temperature disrupted the flowering physiology of strawberry. Under such conditions, the viability and germination of pollen as well as the receptivity of stigma were significantly reduced. The application of titanium organic complex during flowering had a beneficial effect on the pollination and fertilization processes of strawberries. Plants treated with the titanium organic complex were characterized by higher pollen viability, better pollen germination, a higher number of achenes in fruit, and a higher weight of individual fruit, compared to the not treated plants. The obtained results suggest that application of titanium organic complex during flowering may alleviate the stress caused by high temperature and contribute to the improvement of the quantity and quality of a crop.